2019
DOI: 10.1097/md.0000000000017473
|View full text |Cite
|
Sign up to set email alerts
|

Supraglottic devices for airway management in awake craniotomy

Abstract: Awake craniotomy is a unique technique utilized for mapping neuro and motor function during neurosurgical procedures close to eloquent brain tissue. Since active communication is required only during surgical manipulation of eloquent brain tissue and the patient is “sedated” during other parts of the procedure, different methods for anesthesia management have been explored. Furthermore, airway management ranges from spontaneous breathing to oro or nasotracheal intubation. Case reports have described the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Unsuccessful intubation attempts (especially in the presence of posterior airway obstruction) can result in significant oropharyngeal trauma and bleeding, reducing intubation success rate. 12 Although the use of FOB and video laryngoscopy might be preferred to secure a difficult airway in both elective and emergency settings, this approach might not be best for patients during AC. Alternatively, the presence of an LMA, even 1 that is not sealed appropriately to deliver positive pressure ventilation, can significantly displace the tissue in the posterior pharynx and improve the likelihood of successful FOB-assisted intubation when performed through the LMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unsuccessful intubation attempts (especially in the presence of posterior airway obstruction) can result in significant oropharyngeal trauma and bleeding, reducing intubation success rate. 12 Although the use of FOB and video laryngoscopy might be preferred to secure a difficult airway in both elective and emergency settings, this approach might not be best for patients during AC. Alternatively, the presence of an LMA, even 1 that is not sealed appropriately to deliver positive pressure ventilation, can significantly displace the tissue in the posterior pharynx and improve the likelihood of successful FOB-assisted intubation when performed through the LMA.…”
Section: Discussionmentioning
confidence: 99%
“…Displacement of the posterior pharyngeal tissue is difficult with either approach individually, as our simulation demonstrated. Unsuccessful intubation attempts (especially in the presence of posterior airway obstruction) can result in significant oropharyngeal trauma and bleeding, reducing intubation success rate 12…”
Section: Discussionmentioning
confidence: 99%
“…47 Using the fiberoptic bronchoscope, or LMA, as a conduit has been shown to be useful in awake intubation for difficult airways or when the head is fixated on a Mayfield (Integra LifeSciences) during craniotomy. 18 , 48…”
Section: Intraoperative Challengesmentioning
confidence: 99%
“…Airway management during the asleep phase is commonly accomplished with supraglottic airways, such as laryngeal mask airway (LMA), but endotracheal tube or other airway devices have been used. 18 The main challenge of this technique occurs at the emergence from GA and extubation. The key to success is to promote a smooth transition from asleep to awake state.…”
Section: Intraoperative Anesthetic Techniquesmentioning
confidence: 99%
“…The use of supraglottic airway devices (SADs) has been proven to be a feasible airway management method for awake craniotomy (AC) to lower the risk of coughing or gagging during the transition to the awake state[ 1 ]. Recently, a retrospective analysis of 30 cases of AC reported that patients receiving laryngeal mask airway (LMA) had fewer complications and a shorter ventilation duration than patients who underwent fiberoptic intubation[ 2 ]. Considering the requirements of craniotomy and scalp blocks, head rotation and neck flexion may influence the performance of SADs including oropharyngeal leak pressure, ventilation, and fiberoptic view[ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%